STAT5 induces miR-21 expression in cutaneous T cell lymphoma - Lindahl, Lise M.; Fredholm, Simon; Joseph, Claudine; Nielsen, Boye Schnack; Jønson, Lars; Willerslev-Olsen, Andreas; Gluud, Maria; Blümel, Edda; Petersen, David L.; Sibbesen, Nina; Hu, Tengpeng; Nastasi, Claudia; et al. (Impact, 2016)
In cutaneous T cell lymphomas (CTCL), miR-21 is aberrantly expressed in skin and peripheral blood and displays anti-apoptotic properties in malignant T cells. It is, however, unclear exactly which cells express miR-21 and what mechanisms regulate miR-21. Here, we demonstrate miR-21 expression in situ in both malignant and reactive lymphocytes as well as stromal cells. qRT-PCR analysis of 47 patients with mycosis fungoides (MF) and Sezary Syndrome (SS) confirmed an increased miR-21 expression that correlated with progressive disease. In cultured malignant T cells miR-21 expression was inhibited by Tofacitinib (CP-690550), a clinical-grade JAK3 inhibitor. Chromatin immunoprecipitation (ChIP) analysis showed direct binding of STAT5 to the miR-21 promoter. Cytokine starvation ex vivo triggered a decrease in miR-21 expression, whereas IL-2 induced an increased miR-21 expression in primary SS T cells and cultured cytokine-dependent SS cells (SeAx). siRNA-mediated depletion of STAT5 inhibited constitutive- and IL-2-induced miR-21 expression in cytokine-independent and dependent T cell lines, respectively. IL-15 and IL-2 were more potent than IL-21 in inducing miR-21 expression in the cytokine-dependent T cells. In conclusion, we provide first evidence that miR-21 is expressed in situ in CTCL skin lesions, induced by IL-2 and IL-15 cytokines, and is regulated by STAT5 in malignant T cells. Thus, our data provide novel evidence for a pathological role of IL-2Rg cytokines in promoting expression of the oncogenic miR-21 in CTCL.